Adolescent Sexual and Reproductive Health and Rights in Nicaragua : An Analysis Using a Sexual and Reproductive Health Framework and Human Rights - Gordillo-Tobar, Amparo (2015)
In an effort to integrate operational and analytical work on adolescents and youth sexual and reproductive health (SRH) and Human Rights in Nicaragua, the World Bank, in coordination with the Nicaraguan Ministry of Health, the Pan American Health Organization (PAHO), and the United Nations Population Fund (UNFPA) conducted the study titled: sexual and reproductive health among youth in Latin America: adding a human rights perspective. The study was conducted within the umbrella of the ongoing Family Community Health World Bank project. To gain a better understanding of the SRH and Human Rights in the country, the study, funded by the Nordic Development Trust Fund (NTF), reviewed the national legal framework and the school curricula; consulted focus groups for adolescents from representative samples in four geographic regions; and integrated the results of the study into a national multi-sectoral strategy on adolescents sexual and reproductive health and rights (SRHR). The strategy will inform the Bank s operational plans and agreements for the next five years.